Approximation of fixed points for Garcia-Falset mappings in a uniformly convex Banach space - Tanapat Chalarux, Khuanchanok Chaichana (Results in Nonlinear Analysis, 2021)
The aim of this research is to introduce a novel iterative technique termed CC-iteration for identifying the fixed points of Garcia-Falset mappings. In uniformly convex Banach spaces, we establish both weak and strong convergence characteristics. Additionally, numerical examples of the iterative approach are presented in the form of a signal recovery application in a compressed sensing issue.